2
$\begingroup$

I want to solve this differential equation with the power-series method: $$ x^{2}\cdot y''(x) +(1+x^{2}) y'(x) + y(x) =0$$ where $$y(0)=1$$

They want the solution given in elementary functions. I managed to get the recursive formula for $$j\ge 2$$$$a_{j+1} = \frac{-((j(j-1)+1)a_{j} + (j-1)a_{j-1})}{j+1} $$ And also got $$a_{0}=y(0)=1 $$,and then$$ a_{1}=-1, a_{2}=1/2 $$

But Im not sure how to answer in an elementary function, I tried to get some more values and its just irrational values. Appreciate help.

$\endgroup$
1
$\begingroup$

I agree with you're recurrence relation $(i+1)a_{i+1}=-((i^2-i+1)a_i+(i-1)a_{i-1})$. & the first few values $a_0=1, a_1=-1, a_2=1/2, a_3=-1/6$ from this I guess the general formulae $a_i=(-1)^i/i!$. You can easily show (by induction) that this is indeed true. Now the solution is obviously $y=e^{-x}$ & this does indeed satisfy the original equation.

$\endgroup$
9
  • $\begingroup$ But the value I get for $$ a_{4}=-13/24 $$? This doesnt make sense? $\endgroup$ – fejz1234 Jan 29 '17 at 20:18
  • $\begingroup$ Or my bad it is equal to 1/24 actually, but how does one deduce that it is equal to e^(-x) ? $\endgroup$ – fejz1234 Jan 29 '17 at 20:21
  • $\begingroup$ Oh ... let me see what I get ? $4a_4=-(7a_3+2a_2)$ ... $a_4=1/24$ ? $\endgroup$ – Donald Splutterwit Jan 29 '17 at 20:22
  • $\begingroup$ I mean how do you go from $$ \frac{(-1)^{i}}{i!} = e^{-x} $$ , is taylor-expansion that reveals it? $\endgroup$ – fejz1234 Jan 29 '17 at 20:23
  • $\begingroup$ Thats right \begin{eqnarray*} \sum_{i=0}^{\infty} \frac{(-1)^i}{i!}x^i =e^{-x} \end{eqnarray*} $\endgroup$ – Donald Splutterwit Jan 29 '17 at 20:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.